Implementasi Pengelolaan Zakat, Infaq Dan Sedekah Dalam Upaya Pengentasan Kemiskinan Studi Pada: Nu Care - Lazisnu Kabupaten Cilacap - Abas Rosadi (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to analyze the implementation of the collection and distribution of Zakat, Infaq, and Sadaqah (ZIS) funds by NU Care-LAZISNU Cilacap Regency in an effort to alleviate poverty, using the Systematic Literature Review (SLR) approach. The research method is descriptive-analytical, reviewing various literatures such as journals, reports, and related documents to identify patterns, gaps, and program effectiveness. The results showed that NU Care-LAZISNU Cilacap plays a significant role in reducing poverty through economic empowerment programs (such as business capital, MSME training, and mentoring), education (scholarships), health, and social assistance. Based on comparisons with previous research (Fauzi & Rohmah, 2023; Rizky & Kurniasih, 2022; Hidayati, 2023), this program has succeeded in increasing mustahik income by 65%, welfare index by 22%, and encouraging the independence of 70% of assisted MSMEs. However, the main challenges include the low financial literacy of the community, limited human resources of managers, and minimal awareness of zakat. These findings reinforce the theory of economic empowerment (Beik & Arsyianti, 2016) that the productive-consumptive approach is effective in sustainable poverty alleviation. Recommendations include strengthening the socialization of zakat, multi-stakeholder collaboration, and increasing the capacity of managers to optimize the program according to SDGs No Poverty and Decent Work & Economic Growth targets..